Warm Vinegar Fomentation And Conventional Method In Lowering The Body Temperature Among Oregano Phosphorous Poisoning Patients - P Jadhav, Guruprasad; C Gholap, Manisha; P.Patange, Aparna; B Shinde, Mahadeo (International Journal of Psychosocial Rehabilitation, 2024)
Introduction: Organophosphorous poisoning (OPP) is a major community health problem and one of the main problems in the emergency department. Objective: The study investigated the effectiveness of warm vinegar fomentation and conventional methods in lowering the body temperature among oregano-phosphorous poisoning patients. Methods: A post-test only control group design was used to conduct the study among organophosphorous patients. Total of 40 organophosphorous patients were selected by the purposeful sampling technique. Ethical permission was obtained before the data collection. Intensive care unit at a tertiary care hospital, Karad. Warm vinegar fomentation and conventional methods were provided to the OPP patients in the experimental group and control group, respectively. Data was collected by using a structured questionnaire. Results: A significant difference was found between the warm vinegar fermentation and conventional method at the level of p